The lived experience of adolescents with haematological malignancies in Jordan : an interpretive phenomenological analysis study - Al Omari, Omar (Curtin University, 2011)
This thesis explored and documented the lived experiences of Jordanian adolescents with haematological malignancies (HMs). The study explored how these adolescents described their cancer journey throughout the different stages and how these experiences shaped the adolescents’ behavioural responses and coping strategies. A literature review revealed a paucity of bio-psychosocial care studies in this area conducted in Arab countries when compared to western countries. Furthermore, the available research was dominated by quantitative studies, with a dearth of research focused on adolescents with HM. Such a paucity of literature and limited understanding of adolescents’ experiences of living with HM has the potential to compromise the quality of care provided to this group of patients. This study contributes to the understanding of adolescents’ lived experiences and factors that facilitated or inhibited the experience through an in-depth descriptive account.A prospective longitudinal study using an interpretative phenomenological analysis methodology explored the lived experience of 14 Jordanian adolescents with haematological malignancies during the first six months following their diagnosis. In this study, in-depth interviews were the main method of data collection. A total of 27 face-to-face, semi-structured interviews were completed and each interview took on average 75 minutes. Each interview was transcribed verbatim and the data analysis occurred using the interpretive phenomenological analysis method first described by Smith in 1996. The data from transcribed interviews were managed using ©QSR NVivo8 software for qualitative data analysis.The results of the analysis of data were reported under three main themes depicting the participants’ experiences, which were the “silence of HM”, “life is changing”, and “ways of coping”. The analysis indicated that initially the participants received little information and had limited communication with their parents and health team members to assist them to understand what was happening to them. This resulted in the participants experiencing increased levels of distress and feelings of confusion as they were left alone to comprehend the cause of their physical problems. With the onset of cancer treatments, the bio-psychosocial side effects of the chemotherapy became one of the most distressing factors for participants affecting, as it did, all aspects of their lifeworld and generating uncertainty about their futures. Again, participants reported limited support from health team members during this critical stage. This led to difficulties in overcoming the unpleasant experiences associated with chemotherapy and cancer, for example, the alteration in their body image. Nevertheless, the participants were able to adapt and live with their illness with the use of various coping methods. For example, they used their Islamic belief to empower themselves, while playing down the severity of their illness. Some of them used hospital resources, such as the creativity room at the hospital to assist them to cope with the daily impact of their illness and maintain a sense of normality.The results of this study were consistent with previous research findings, highlighting a number of areas requiring further attention from Jordanian health planners and health team members responsible for caring for adolescents with haematological malignancies. For example, health team members need to place emphasis on the provision of psychosocial care for adolescents in order to prevent the development of co-morbidities during the illness journey. Health team members should also adopt a family centered approach to care to reduce the stress and concern of both the adolescents and their parents. In general, health team members, communities and schools need to work in collaboration in order to effectively provide adolescents with holistic care. The findings have added significantly to existing knowledge and understanding of the spiritual and psychosocial needs of adolescents during this time, particularly because this is the first qualitative research study conducted in Jordan in this area of health care.This thesis has limitations of which one was that due to hospital policy some of the participants’ parents attended the two data collection periods and their presence may have impacted of the experiences expressed. The thesis concludes with a discussion of practice changes and future research projects in this area. Additional longitudinal, qualitative and prospective research studies are needed to explore the lived experiences of adolescents with HM to further identify the bio-psychosocial developmental changes that they experience during their illness journey.